2013
DOI: 10.5713/ajas.2012.12636
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Thyme and Cinnamon Essential Oils on Performance, Rumen Fermentation and Blood Metabolites in Holstein Calves Consuming High Concentrate Diet

Abstract: Essential oils have been shown to favorably effect in vitro ruminal fermentation, but there are few in vivo studies that have examined animal responses. The objective of this study was to evaluate the effects of thyme (THY) and cinnamon (CIN) essential oils on feed intake, growth performance, ruminal fermentation and blood metabolites in feedlot calves fed high-concentrate diets. Twelve growing Holstein calves (213±17 kg initial BW) were used in a completely randomized design and received their respective diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

31
84
3
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(127 citation statements)
references
References 52 publications
31
84
3
9
Order By: Relevance
“…In this study, the addition of TS essential oil at the levels of 10 and 15 μl per kg LW of lambs did not adversely affect LW or LW gain. The intake of concentrate feed and lucerne hay was similar which is in accordance with the results of other in vivo studies examining thyme oil and active compounds of this genus (carvacrol, thymol, γ-terpenene and p-cymene) (Bampidis et al, 2005;Chaves et al, 2008;Wang et al, 2009;Vakili et al, 2013). Simitzis et al (2008) also observed that supplementation of concentrate feed oregano essential oil (1 ml · kg −1 ) did not affect LW or LW gain.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, the addition of TS essential oil at the levels of 10 and 15 μl per kg LW of lambs did not adversely affect LW or LW gain. The intake of concentrate feed and lucerne hay was similar which is in accordance with the results of other in vivo studies examining thyme oil and active compounds of this genus (carvacrol, thymol, γ-terpenene and p-cymene) (Bampidis et al, 2005;Chaves et al, 2008;Wang et al, 2009;Vakili et al, 2013). Simitzis et al (2008) also observed that supplementation of concentrate feed oregano essential oil (1 ml · kg −1 ) did not affect LW or LW gain.…”
Section: Discussionsupporting
confidence: 89%
“…Chaves et al (2008) found that carvacrol (purity >98%) supplementation at the level of 0.2 g · kg −1 DM reduced ruminal pH, increased VFA and did not change A:P ratio or NH 3 -N level in lambs. Besides, thyme essential oil (5 g · d −1 · calf −1 ) supplementation to growing calves diet (15% lucerne hay and 85% concentrate feed) did not affect pH value, concentration of NH 3 -N and molar concentration of VFA in rumen fluid; whereas decreased the molar proportion of acetate and A:P ratio, and increased the molar proportion of propionate (Vakili et al, 2013). In another study, addition of Origanum vulgare oil (rich in carvacrol) into lamb diet increased pH value, NH 3 -N concentration, and the molar concentration of VFA in rumen fluid (Biricik et al, 2016).…”
Section: Discussionmentioning
confidence: 90%
“…Vakili et al (23) established that thyme essential oil in the diets of feedlot calves (5 g/day/calf) resulted in no changes in values of plasma total cholesterol and triglyceride. Whereas in another study it has been reported that, concentrations of trigycerides can be influenced by essential oil supplementation via changing of feed intake (25).…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy might be explained by differences in the experimental procedure kind of animals, physiological status and various compounds used. Vakili et al (2013) reported that thyme in the diet of feedlot calves resulted in no changes in values of plasma total cholesterol and triglyceride. In the present study, WBC count was significantly higher in rams when essential oil was supplemented at the rate of 20 ml/kg.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Vakili et al (2013) reported that thyme in the diet of feedlot calves resulted in no changes in plasma total cholesterol and triglyceride. Also, Vakili et al (2013) reported that thyme in the diet of feedlot calves resulted in no changes in values of plasma total cholesterol and triglyceride.…”
Section: Discussionmentioning
confidence: 99%